Effect of voice therapy with or without transcutaneous electrical stimulation on recovery of injured macroscopically intact recurrent laryngeal nerve after thyroid surgery - Formánek, Martin; Walderová, Radana; Baníková, Šárka; Chmelová, Irina; Formánková, Debora; Zeleník, Karol; Komínek, Pavel (European archives of oto-rhino-laryngology, 2020)
PURPOSE: Electrical stimulation-supported therapy is an often used modality. However, it still belongs to experimental methods in the human larynx. Data are lacking with which to evaluate the real effect in recurrent laryngeal nerve injury. The aim of this study was to investigate whether transcutaneous electrical stimulation added to voice therapy has a beneficial effect compared to voice therapy alone on vocal fold movement recovery in the case of an injured macroscopically intact recurrent laryngeal nerve. METHODS: Adults with unilateral vocal fold paralysis after thyroidectomy, in which the recurrent laryngeal nerve was left macroscopically intact, were included in this case-control study performed in tertiary referral hospital between September 2006 and June 2018. Among 175 eligible participants, 158 were included. Compliance with 6 months follow-up was 94.3%. INTERVENTIONS: medicament therapy and voice therapy (group 1) vs. medicament therapy and voice therapy and transcutaneous electrical stimulation (group 2). MAIN OUTCOME: vocal fold movement. RESULTS: A total of 149 patients were included in the analysis (group 1, 89 patients; group 2, 60 patients). The groups were homogenous. In groups 1 and 2, 64% and 60% of vocal folds, respectively, were improved after 6 months (P = 0.617). No difference was found between patients who improved and patients who did not improve. CONCLUSIONS: Adding transcutaneous electrical stimulation to voice therapy provided no beneficial effect on the recovery of vocal fold movement. Therefore, its indications should be re-evaluated; it is questionable whether stimulation should be routinely recommended.
Keywords: Thyroid Gland; štítná žláza; Transcutaneous Electric Nerve Stimulation; Vocal Cord Paralysis; nervus laryngeus recurrens; Electrical stimulation; ochrnutí hlasivek; transkutánní elektrická neurostimulace; Adult; Case-Control Studies; dospělí; Vocal cord paralysis; Recurrent Laryngeal Nerve; lidé; studie případů a kontrol; Recurrent laryngeal nerve; Humans; Treatment outcome; Voice training; Transcutaneous electrical nerve stimulation